2017
DOI: 10.4236/jss.2017.57024
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Sense of Community Responsibility and Diversity in Old Age: A Qualitative Study of Urban Older Adults in India

Abstract: The aim of the present study is to explore older adult people's meaning of psychological sense of community (PSOC), a key element in individual and community well-being. Using thematic and discourse analytical approaches we have in an in-depth and context-sensitive way analyzed interview material from twelve urban older informants residing in the heterogenic mega-city of Mumbai. Several themes included in the samples meaning of PSOC confirm established dimensions of the concept. However, key aspects of their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Their findings are consistent not only with the four dimensions (i.e., needs fulfillment, group membership, influence, and shared emotional connection) in McMillan and Chavis’ () theory, but respondents emphasized the importance of responsibility to the community, thus lending support to Nowell and Boyd's () conception of SOC‐R. Bahl and Hagen () suggested this finding mirrors the values of collectivism salient in Indian culture, and reflects the context‐sensitive nature of the SOC‐R construct. In their mixed‐methods study, Lowe, Stanley, and Stanley () interviewed bus operators about their interactions with their community and found that people expressed feelings of duty and responsibility toward their community.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Their findings are consistent not only with the four dimensions (i.e., needs fulfillment, group membership, influence, and shared emotional connection) in McMillan and Chavis’ () theory, but respondents emphasized the importance of responsibility to the community, thus lending support to Nowell and Boyd's () conception of SOC‐R. Bahl and Hagen () suggested this finding mirrors the values of collectivism salient in Indian culture, and reflects the context‐sensitive nature of the SOC‐R construct. In their mixed‐methods study, Lowe, Stanley, and Stanley () interviewed bus operators about their interactions with their community and found that people expressed feelings of duty and responsibility toward their community.…”
Section: Introductionsupporting
confidence: 64%
“…Since Nowell and Boyd () first conceptualized SOC‐R, a number of qualitative and quantitative studies have further explored and empirically tested the construct. In a qualitative study, Bahl and Hagen () examined the meaning of sense of community among a small sample of older adults in India. Their findings are consistent not only with the four dimensions (i.e., needs fulfillment, group membership, influence, and shared emotional connection) in McMillan and Chavis’ () theory, but respondents emphasized the importance of responsibility to the community, thus lending support to Nowell and Boyd's () conception of SOC‐R.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have highlighted the importance of trust and community involvement in reducing the odds of low psychological health low subjective well-being among older adults [ 51 , 52 ]. Trust and community involvement provide a sense of security and comfort that further improves psychological health and subjective well-being among older adults [ 53 ]. Results found state-wise differential in low psychological health and low subjective well-being among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study indicated that the sense of responsibility had cross-context consistency: An individual's sense of responsibility in one context (e.g., family) had a strong predictive effect on his sense of responsibility in another context [34]. People not only have a need to be a part of community but also feel a sense of duty and responsibility toward their community [35,36]. Therefore, perhaps we can speculate on the relationship between SOC-R and altruistic behavior from studies of family responsibility and social responsibility.…”
Section: Introductionmentioning
confidence: 99%